Linear DNA–Chitosan Nanoparticles: Formulation Challenges and Transfection Efficiency in Lung Cell Line - Chiara Migone; Angela Fabiano; Ylenia Zambito; Rebecca Piccarducci; Laura Marchetti; Chiara Giacomelli; Claudia Martini; Anna Maria Piras (Applied Biosciences)
Linear DNA constructs are used in gene delivery and therapy application due to their capacity of integration into the mammalian genome, offering stable transgene expression. Compared to circular plasmids, linear DNA also has the advantage that its dimension and steric hindrance are directly correlated to the length of the nucleotide chain. These considerations make linear DNA an effective choice for gene delivery pilot studies, where formulations and transfection efficiency calculations are studied considering the nucleic acid dimensions. Meanwhile, the development of DNA–chitosan nanoparticles (NPs) has gained significant interest for their potential in nucleic acid delivery, especially as non-viral gene delivery systems and for embedding linear DNA fragments, as well as gene delivery to the lung. This study explored an easy polyelectrolyte complexing preparation of linear DNA-loaded chitosan nanoparticles. Among the different formulations of nanoparticles prepared, the optimal one exhibited a size of approximately 290 nm, an encapsulation efficiency of 86% and a zeta potential of 25 mV. Additionally, this study examined how the concentration of DNA in solution influenced nanoparticle formation, encapsulation efficiency and particle size. In particular, transient transfection of the chitosan–linear DNA fragment complex, encoding for green fluorescent protein (GFP), was conducted in human pulmonary distal lung cells (NCI-H441 cells), demonstrating successful cellular internalization and protein expression. These studies highlight the potential of DNA–chitosan NPs in nucleic acid delivery, particularly for pulmonary applications. Future works will focus on formulating the achieved carrier into an inhalable dosage form to improve its translational application.